Analisis Kebutuhan Media Pembelajaran Sejarah Kebudayaan Islam Melalui Aplikasi Canva di MIN 03 Kepahiang - Reki Tri Andriani; Aida Rahmi Nasution; Kusen Kusen (Jurnal Budi Pekerti Agama Islam, 2024)
Education which is dynamic, always developing requires developments in every aspect, including learning media. Learning media is a component that has an important role in supporting successful learning. War learning media as a means of distribution tool used by lecturers and acts as a facilitator in the learning process to convey lesson material to students. The purpose of this research is to determine the analysis of the need for learning media for the history of Islamic culture through the Canva application at MIN 03 Kepahiang. This research is a quantitative research using a Linkert scale which was distributed to 26 class IV A students at MIN 03 Kepahiang. The results of this research showed that material analysis was at 93.8%, tools and teaching materials at 93.6% and strategies at 95.4% as well as an interval of 80-100%, which means students really need updates in learning media.